Impact of Non-Governmental-Based Supporting Group toward Resilience Level among People with HIV AIDS in Indonesia - Arif Gustyawan; Emi Wuri Wuryaningsih; Dicky Endrian Kurniawan (Nursing and Health Sciences Journal (NHSJ), 2022)
The problem faced by the government is the limitation to support PLWHA to enhance their mental health status. The non-governmental-based supporting group may have an impact on PLWHA’s resilience due to their psychosocial problems. The purpose of this study was to explore the resilience levels among people with HIV/AIDS (PLWHA) who are members of a non-governmental-based supporting group. This study used a quantitative design with a descriptive explorative approach — a hundred PLWHA, who have registered and followed the non-governmental supporting group in Jember, Indonesia during the last period of 2018 following this study by using a purposive sampling technique. The Brief Resilience Scale questionnaire was used to collect data. Data was collected in June - July 2019. Data were analyzed by descriptive explorative approach with 95% of CI and data were shown in the frequency table. The results of this study showed that 3% of the respondents’ resilience has low resilience category, 56% has normal resilience, and 41% has high resilience level after 6 months following the supporting group. Support from members of the supporting group as an external factor made respondents more resilient. Resilience for PLWHA should be further enhanced to help PLWHA survive better and be able to face difficulties.